Carrying Capacity of Water Resources for Renewable Energy Development in Arid Regions in Northwest China: A Case Study of Golmud, Qinghai - Hou, Wenjuan; Li, Xiaojie; Yang, Linsheng; Ta, Wanquan; Jia, Xiaopeng (Frontiers in Environmental Science, 2022)
Abstract: Northwest China has become a base for wind and solar energy development due to its rich wind and solar resources and large area of desert and unutilized land. However, whether the scarce water resources in the arid regions there can meet the requirements for renewable energy development is currently a pressing, critical problem. Therefore, the life cycle water footprint (WF) of the renewable energy industry—its wind energy, photovoltaic (PV), and concentrated solar power (CSP) electricity generation enterprises—in the basin area of Golmud, Qinghai, a typical arid region in Northwest China, has been investigated in this study. Water consumption by local renewable energy enterprises was estimated under current (2020) scenarios [i.e., different (local/vs. nonlocal) origins of equipment and raw materials used, and employees hired by these enterprises] and three future scenarios (i.e., different ratios between installed capacities of wind energy, PV, and CSP at a fixed total renewable energy electricity generation capacity assuming China’s carbon emission will peak then). The results revealed that water consumption by local renewable energy enterprises in 2020 was 1.62 × 106–1.31 × 107 m3, accounting for 0.07–0.6% of the current total water resources in the basin area of Golmud. Water consumption by the local salt chemistry industry, a pillar industry in Golmud whose water consumption is high, accounted for 2.69% of the total water resources being 4.24–34.37 times that of the local renewable energy industry. To reach the goal of carbon emissions peaking by 2030 requires an increase of 6.17 × 106 kW in the installed capacity for wind and solar power generation in Golmud, would translate into an increase of 1.57 × 107–6.46 × 107 m3 in water consumption, this accounting for 7.15–19.35% of the remaining available water resources in the basin area of Golmud. Our results indicate that the expansion of the local renewable energy industry has exerted significant pressure on the already scarce water resources in Golmud. Therefore, future increases in the installed capacity for renewable energy electricity generation should be planned scientifically, by considering the availability of water resources as a constraint.